PENTINGNYA MOTIVASI DALAM PENINGKATAN PRODUKTIVITAS KERJA BAGIAN SORTING AND PACKING PT. DHARMA PERKASA GEMILANG, MULIAKERAMIK GROUP, NGORO – JAWA TIMUR - Rizky Ananda Putri; Indriati Paskarini (JURNAL PENELITIAN KESEHATAN, 2017)
Labor holds crucial and notable function as both the subject and goal of the development due to the quality of human resource and high productivity encompassed on it. One of the factors of high productivity is work motivation. The purpose of this research was to determine the correlation between Work Motivation with Work Productivity in Sorting And Packing Department of Dharma Gemilang Perkasa Company, Muliakeramik Group, in Ngoro - East Java. This research was an analytic observational research with spearman’s correlation approach. The samples in this research is 13 workers in sorting and packing division in PT. Dharma Perkasa Gemilang, Muliakeramik Group, Ngoro – East Java. The variables are individual characteristic (age and period of work), work motivation, and work productivity. Meanwhile, the instrument of this study is the measurement of work motivation by filling the questionnaire. The data are analyzed by univariate and bivariate (using Spearman correlation test with α= 0,01). The results showed that there was statistically positive correlation between work motivation and work productivity (p- value 0,004) and correlation value r = 0,732 which meant that there was a strong relation between work motivation and work productivity. Conclusion of this research is work motivation had positive effect on work productivity. It can be suggested that PT. Dharma Perkasa Gemilang, Muliakeramik Group, Ngoro- East Java need to provide enhancement of labor’s work motivation in order to gain high productivity, which are escalation of maintenance quality in the form of performance evaluation, payment, or salary according to Regional Minimum SalaryKeywords: Individual Characteristics, Works Motivation, Works Productivity